Forms of Violation of Law of the Republic of Indonesia Number 24 of 2009 Concerning the Use of Indonesian as Geographical Names in Indonesia - Fauzi, Aziz; Prima Sintasari, Diardana (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
The use of Indonesian by the general public today is still very inappropriate. The phenomenon of language use in public spaces which includes many spelling errors, vocabulary and Indonesian structure. Good and correct use of Indonesian is often hindered by the presence of other languages. Researchers will try to explain the form of non-compliance from the mandate of Law of the Republic of Indonesia No. 24 of 2019 concerning